



 
Hi Joey, I'm going to solve a similar problem.
This is an application of the chain rule. What you need to see is that this is a function f(x), raised to a power. You have f(x) = 1/2 x^{3}  x^{2} + 3 raised to the sixth power. The chain rule for functions of the form [f(x)]^{n} states that
In my problem n = 6 and f(x) = 1/2 x^{3}  x^{2} + 3 so f '(x) = 3/2 x^{2}  2x. Thus
Now try your problem,  


Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences. 